THE USE OF TRANSLANGUAGING AS A PEDAGOGICAL STRATEGY IN EFL CLASSROOM: A CASE STUDY AT BULUKUMBA REGENCY - Rahmawansyah Bin Sahib (LET: Linguistics, Literature and English Teaching Journal, 2019)
This study investigates the use of Translanguaging as a Pedagogical Strategy by an EFL teacher in terms of interaction between the teacher and the students in teaching and learning process. It focuses to explore in what situation, do the practices of translanguaging which go on in EFL classroom. This study applied qualitative method. Two meetings of classroom observations were recorded by using audio recorder. Also, a teacher and ten students were interviewed after the classroom observation. The recordings and interviews were transcribed and analyzed based on in what situation, do the the practices of translanguaging go on in EFL classroom. In the research findings there were three kinds of languages namely English as the Foreign language, Indonesia as the national language, and Konjo as the local language that used by the teacher and students in practice of translanguaging during teaching and learning process in EFL Classroom. Therefore, the researcher found that the teacher used translanguaging in seven situations during teaching process. And students used translanguaging in six situations during the teaching and learning process.